Surgical management for inferior turbinate hypertrophy: a narrative review - Divya, Mano Leoni; Rajasekaran, Valli; Prakash, D. Y. Raj (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Inferior turbinate hypertrophy can lead to bothersome symptoms of the nose. Inferior turbinate reduction has to be treated surgically for cases, which are refractory to medical treatment. Plethora of surgical techniques have evolved over the recent years to surgically treat inferior turbinate hypertrophy. Yet, there remains a lack of consensus on optimal surgical technique or a cumulative study on the merits and demerits of the surgical procedures performed. The aim of the study was to review 26 articles from time period of January 2000 to January 2021 studied on surgical techniques of turbinate reduction. On reviewing the studies, it was noted that conventional turbinectomy techniques were not preferred by surgeons to avoid chances of severe complications and hence more studies on newer advanced techniques were noted. Among the newer techniques to find an adequate balance between nasal physiology and tissue preservation RFTVR is preferred and is the optimal technique owing to its minimal invasion, performance ease and reduced complications. Most recent studies represent the benefits of RFTVR.